2018
DOI: 10.21873/cgp.20087
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Clonality Between Components of Combined Hepatocellular Carcinoma and Cholangiocarcinoma by Targeted Sequencing

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…DNA and RNA were quantified using the Qubit 2.0 Fluorometer (Thermo Fisher Scientific). DNA and RNA libraries were prepared as previously described (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). These DNA libraries were generated from 20 ng of DNA per sample using an Ion AmpliSeq Library Kit 2.0 (Thermo Fisher Scientific) and the Oncomine Comprehensive Assay v1 (OCA v1) panel (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA and RNA were quantified using the Qubit 2.0 Fluorometer (Thermo Fisher Scientific). DNA and RNA libraries were prepared as previously described (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). These DNA libraries were generated from 20 ng of DNA per sample using an Ion AmpliSeq Library Kit 2.0 (Thermo Fisher Scientific) and the Oncomine Comprehensive Assay v1 (OCA v1) panel (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the sequencing data was performed using the Torrent Suite Software v5.2.2 (Thermo Fisher Scientific). This workflow was created by adding a custom hotspot Browser Extensible Data file to report mutations of interest and a custom CNA baseline (described below) using the manufacturer's default workflow, as described previously (24,25,35). The pipeline used included signaling processing, base calling, quality score assignment, adapter trimming, read mapping to the human genome assembly GRCh37, quality control of mapping, coverage analysis with downsampling, and variant calling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as the histological aspects in cHCC-CCA vary, so does the molecular profile. 31,32,34,[36][37][38][39][40][41][42] Previous studies found that the genetics of cHCC-CCA were closer to iCCA than HCC. 42 However, the recent study performed by Joseph et al showed that the genetics of cHCC-CCA, classical type, are distinct from iCCA but similar to HCC, for example, alterations in TERT, TP53, cell cycle genes (CCND1, CCNE1, CDKN2A), receptor tyrosine kinase/Ras/PI3-kinase pathway genes (MET, ERBB2, KRAS, PTEN).…”
Section: Molecular Profiles (►Table 2)mentioning
confidence: 99%
“…DNA and RNA were quantified using the Qubit 2.0 Fluorometer (Thermo Fisher Scientific). DNA and RNA libraries were prepared as previously described (6,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). These DNA libraries were generated from 20 ng of DNA per sample using an Ion AmpliSeq Library Kit 2.0 (Thermo Fisher Scientific) and Oncomine Comprehensive Assay (OCA) v1 panel (Thermo Fisher Scientific).…”
Section: Materials and μEthodsmentioning
confidence: 99%